Raúl Antelo’s (Post)Critical Interventions: Crítica acéfala, Archifilologías latinoamericanas y A ruinologia (2016) (Anclajes, 2024)
Starting from a question about the "diasporic" position of certain authors of cultural criticism in Latin America, always halfway between academic affiliation and a kind of fractious position regarding their increasingly bureaucratized practices of knowledge administration, this paper proposes a reading of three representative texts by the Brazilian-Argentine critic Raul Antelo: Crítica acéfala, Archifilologías latinoamericanas. Lecturas tras el agotamiento and A ruinologia. These strange and problematic texts seem to be articulated from a position that not only (post)critically revises the foundations of more conventional criticism, but also moves toward the behavior of the most radical bids of artistic conceptualism; in other words, in them criticism becomes an act: intervention. And therein lies its forceful emergence in the framework of contemporary literary and cultural studies.
Keywords: Raúl Antelo; Latin American cultural criticism; Crítica acéfala; Archifilologías latinoamericanas; A ruinologia